Neural correlates of intersensory processing in 5‐month‐old infants. Issue 3 (19th February 2013) - Reynolds, Greg D.; Bahrick, Lorraine E.; Lickliter, Robert; Guy, Maggie W.
Abstract Two experiments assessing event‐related potentials in 5‐month‐old infants were conducted to examine neural correlates of attentional salience and efficiency of processing of a visual event (woman speaking) paired with redundant (synchronous) speech, nonredundant (asynchronous) speech, or no speech. In Experiment 1, the Nc component associated with attentional salience was greater in amplitude following synchronous audiovisual as compared with asynchronous audiovisual and unimodal visual presentations. A block design was utilized in Experiment 2 to examine efficiency of processing of a visual event. Only infants exposed to synchronous audiovisual speech demonstrated a significant reduction in amplitude of the late slow wave associated with successful stimulus processing and recognition memory from early to late blocks of trials. These findings indicate that events that provide intersensory redundancy are associated with enhanced neural responsiveness indicative of greater attentional salience and more efficient stimulus processing as compared with the same events when they provide no intersensory redundancy in 5‐month‐old infants. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc. Dev Psychobiol 56: 355–372, 2014.